Factors influencing digital health literacy among older adults: a scoping review - Shi, Zhen; Du, Xixi; Li, Juan; Hou, Rongting; Sun, Jingxuan; Marohabutr, Thammarat (Frontiers in Public Health, 2024)
BackgroundThe growth of digital technology, represented by the development of the Internet, has become popular among older adults. Implying digital health literacy on older adults also affects their ability to use digital technology to search, browse, understand, and evaluate health information to improve their health status. This scoping review aims to explore (1) the situation of digital health literacy among older adults and (2) the influencing factors on the digital health literacy of older adults.MethodsA scoping review was performed to evaluate evidence on influencing factors on digital health literacy among older adults in October 2023 employing data from literature indexed in PubMed, Web of Science, EBSCO, Springer Link, and CNKI with search terms such as “digital health literacy,” “e-health literacy,” “eHealth literacy” and “elderly people,” “aged people,” “old age.” The review comprised research articles that addressed issues related to digital health literacy and older adults, excluding non-research and research articles that only expressed opinions without concrete data or material support.ResultsThe final review included 28 articles from 4,706 retrieved records. The synthesis revealed that the digital health literacy of older adults was reflected in the scores of older adults in high-income countries, which were relatively high. In contrast, those in middle-income countries tended to be generally lower. The digital health literacy of older adults was affected by socio-demographic factors, related factors of electronic devices, and use and social support factors.ConclusionGaps of study discussed in this scoping review should be narrowed in further studies. Developing digital health literacy interventions with education and training programs should be considered to improve the digital health literacy of older adults. The digital divide among older adults should be bridged by improving social capital and family support through integrated intervention roles of government, community, and family.